Nutritional considerations for female athletes in weight category sports - Langan-Evans, C.; Reale, R.; Sullivan, J.; Martin, D. (European Journal of Sport Science, 2022)
Weight making can be described as the process of reducing body mass in events where aesthetics, propulsion or the requirement to meet a specific weight category limit, are considered to be of competitive importance. Cross sectional research specifically focussed on weight category sports, has highlighted behaviours and practices that are similar in athletes of both sexes. Regardless of this and despite parallel participation in weight category sporting events, females are drastically underrepresented in studies examining body mass loss interventions across both chronic and acute timeframes. However, it has been well characterised that these types of body mass loss strategies can be causative of low energy availability, leading to consequences of female athlete triad and relative energy deficiency in sports. Furthermore, female specific body composition and physiological systems modulated by the anterior pituitary and ovarian hormones within the menstrual cycle or use of hormonal contraception, can lead to potential outcomes which need to be considered carefully, particularly when employing acute weight loss strategies that are often utilised by weight making athletes. Therefore, the aim of this article serves to review the aforementioned issues, whilst offering practical recommendations via initial assessment, chronic/acute interventions and refeeding/recovery plans to help support the implementation of body mass loss strategies in the context of weight making specifically with female athletes.